2015
DOI: 10.4049/jimmunol.1402604
|View full text |Cite
|
Sign up to set email alerts
|

Oil-in-Water Emulsion MF59 Increases Germinal Center B Cell Differentiation and Persistence in Response to Vaccination

Abstract: Induction of persistent protective immune responses is a key attribute of a successful vaccine formulation. MF59 adjuvant, an oil-in-water emulsion used in human vaccines, is known to induce persistent high-affinity functional Ab titers and memory B cells, but how it really shapes the Ag-specific B cell compartment is poorly documented. In this study, we characterized the Ab- and Ag-specific B cell compartment in wild-type mice immunized with HlaH35L, a Staphylococcus aureus Ag known to induce measurable funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 47 publications
4
53
1
Order By: Relevance
“…We found that induction of SIV mac239 Env-specific IL-21 + T FH cells was not as robust following the boosting immunizations compared to the induction following the Ad5hr-recombinant priming. Yet MF59, the adjuvant used for protein boosting in this pre-clinical vaccine study, has been shown to promote GC B cell differentiation and T FH induction (43, 44). It may be that the modest elicitation of SIV mac239 Env-specific compared to the SIV smH4 Env-specific IL-21 + T FH cells reflects a difference between persistent antigen exposure from Ad5hr-SIV env recombinant and short-term antigen exposure from the Env protein boosts.…”
Section: Discussionmentioning
confidence: 95%
“…We found that induction of SIV mac239 Env-specific IL-21 + T FH cells was not as robust following the boosting immunizations compared to the induction following the Ad5hr-recombinant priming. Yet MF59, the adjuvant used for protein boosting in this pre-clinical vaccine study, has been shown to promote GC B cell differentiation and T FH induction (43, 44). It may be that the modest elicitation of SIV mac239 Env-specific compared to the SIV smH4 Env-specific IL-21 + T FH cells reflects a difference between persistent antigen exposure from Ad5hr-SIV env recombinant and short-term antigen exposure from the Env protein boosts.…”
Section: Discussionmentioning
confidence: 95%
“…However, meningococcal conjugate vaccines in humans have been shown to induce longlasting protection [46,47], even after a single dose [48], while in our model a low B cell memory to the polysaccharide has been observed. This difference may be partially explained by the use of a single glycoconjugate dose, therefore a booster dose might be necessary to achieve high anti-polysaccharide response [49], or a more potent adjuvant could be used to increase the mouse immunological response [29]. The interference caused by circulating anti-carrier antibodies has also been recently described in humans: maternal antibodies elicited by a combined diphtheriatetanus-acellular pertussis-inactivated polio vaccine have been observed to interfere with the neonatal immune response to a following meningococcal C-CRM 197 conjugate immunization [50].…”
Section: Discussionmentioning
confidence: 98%
“…For the characterization of antigen-specific T h cell responses, cell suspension of mice spleens harvested at day 35 were prepared as reported [29], stained with a fluorescent-labeled antibody mix and analyzed on a special-order FACS LSRII instrument (BD Biosciences). A gating strategy to identify the interleukin-producing T h cells and a Boolean gating strategy to distinguish T h 1 and T h 2 responses were applied (details in SI).…”
Section: T H Analysis By Flow Cytometrymentioning
confidence: 99%
“…Pre-clinical and clinical studies of SUD vaccines showed that post-immunization anti-drug Ab levels and affinity vary greatly across subjects, but the cause of such variability is not clear. 10 Before and after immunization, the number of antigen-specific B and T cells in the total lymphocyte repertoire varies in individual mice 33,[36][37][38][39][52][53][54][55][56][57][58] and in human subjects. 59,60 Consistently, individual variability of similar magnitude has been found in the polyclonal hapten-specific B cell population in blood, peripheral lymph nodes and spleen of various mouse strains, before and after immunization with vaccines for oxycodone and nicotine.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%
“…67 Development of SUD vaccines could also benefit from testing other adjuvants of interest, which are at different stages of development or regulatory approval. 106 For instance, the Food and Drug Administration (FDA) recently approved MF59, a squalene-based oil-in-water emulsion used in influenza vaccines, which promotes GC B cell and T fh cell responses, 52,107 key features for generation of highaffinity Ab.…”
mentioning
confidence: 99%